Digital Architectural Heritage in Saudi Arabia: An Integrated Model for Documentation and Preservation - A. Mulush; A. Baik (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The Kingdom of Saudi Arabia boasts a rich architectural heritage encompassing traditional Najdi mud houses, Islamic-era structures, and modern historical landmarks. Documenting and preserving this heritage are vital for understanding Saudi cultural identity and ensuring sustainable conservation. This paper introduces an integrated model for the digital documentation and preservation of architectural heritage, leveraging technologies such as Heritage Building Information Modelling (HBIM), 3D laser scanning, and Geographic Information Systems (GIS). Case studies include Al-Balad Historic Jeddah, Diriyah’s At-Turaif District, and the mud-built structures of Al-Qassim. The model emphasizes a holistic approach that integrates high-resolution 3D documentation, heritage analysis, and stakeholder collaboration. By bridging gaps between digital tools and conservation strategies, this study contributes to the broader discourse on how digital methodologies can protect Saudi Arabia’s architectural heritage for future generations.